The Effect of Picture and Picture Media on Understanding Writing Procedural Texts among Eighth-Grade Students at SMP HKBP Batu 4 - Sinaga, Lambok Hasudungan Pratama Yuda; Manihuruk, Leonita Maria Efipanias; Hutahaean, David Togi; Siahaan, Mungkap Mangapul; Purba, Christian Neni; Pasaribu, Sunggul (Fakultas Keguruan dan Ilmu Pendidikan, Universitas Pahlawan Tuanku Tambusai, 2024)
This research was carried out to find out the Effect of Picture and Picture Media on Understanding Writing Procedure Text at Grade Eight students of SMP HKBP Batu 4. The research methodology used in this research was a quantitative method. The population of this research was at grade VIII of SMP HKBP Batu 4 in the academic year 2024/2025. The researcher took two classes as the sample. The samples were VIII-A as experimental group consisted of 25 students and VIII-B as control group consisted of 25 students. Data collection was carried out using essay tests. The data were obtained by using pre-test and post-test given to both groups, score were calculated and analyzed using excel and manual method. The research results showed that the average score of the experimental class was a pre- test score of 63 and post-test score of 82.68. Meanwhile, the average score for the control class was a pre-test score of 57.56 and post-test 74.12. The t-test calculation shows that (8.8>2.068) at a significance level of 2.5%, a two-sided test means the null hypothesis (HO) is rejected and the alternative hypothesis (Ha) is accepted. This means that the effect of Picture and Picture on Understanding Writing Procedure Text at Grade Eight Students of SMP HKBP Batu 4.